2017
DOI: 10.1007/s10689-017-9984-y
|View full text |Cite
|
Sign up to set email alerts
|

A new POT1 germline mutation—expanding the spectrum of POT1-associated cancers

Abstract: Melanomas are associated with several hereditary conditions. We present a large family with several family members affected with primary melanomas and dysplastic nevi as well as thyroid cancer and other malignant tumors. Clinical work-up did not reveal a mutation in any of the genes usually considered with evaluation for predisposition to melanoma (BRCA1/2, CDKN2A, CDK4, PTEN, TP53). Whole exome sequencing of five affected family members showed a new variant in POT1. POT1 is associated with the telomere shelte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…POT1 is a gene involved in telomeres maintenance, a critical function for genome stability, having a significant intolerance to LoF variants (GnomAD v.2.1: observed vs. expected ratio: 0.19). Multiple reports associated POT1 germline variants with various types of familial cancers including chronic lymphocytic leukemia (CLL; Speedy et al, 2016), Hodgkin lymphoma (McMaster et al, 2018), glioma (Bainbridge et al, 2015), melanoma (Muller, Krunic, Wendt, von Haeseler, & Okamoto, 2018; Potrony et al, 2018; Robles‐Espinoza et al, 2014; Shi et al, 2014; Wilson et al, 2017; Wong et al, 2018), cardiac angiosarcoma (Calvete et al, 2015), Li‐Fraumeni‐like syndrome (Calvete et al, 2017) and CRC (Chubb, Broderick, Dobbins, Frampton et al, 2016). Chubb et al, reported the presence of three carriers of Type‐A/B variants among cases: c.219_220insA (p.Asn75LysfsTer16, cpMAF:0%), c.1087C>T (p.Arg363Ter, cpMAF:0.001%) and c.1851_1852delTA (p.Asp617GlufsTer9, cpMAF:0.004%), while no Type‐A/B variants were identified in controls (Chubb, Broderick, Dobbins, Frampton et al, 2016; CanVar).…”
Section: Resultsmentioning
confidence: 99%
“…POT1 is a gene involved in telomeres maintenance, a critical function for genome stability, having a significant intolerance to LoF variants (GnomAD v.2.1: observed vs. expected ratio: 0.19). Multiple reports associated POT1 germline variants with various types of familial cancers including chronic lymphocytic leukemia (CLL; Speedy et al, 2016), Hodgkin lymphoma (McMaster et al, 2018), glioma (Bainbridge et al, 2015), melanoma (Muller, Krunic, Wendt, von Haeseler, & Okamoto, 2018; Potrony et al, 2018; Robles‐Espinoza et al, 2014; Shi et al, 2014; Wilson et al, 2017; Wong et al, 2018), cardiac angiosarcoma (Calvete et al, 2015), Li‐Fraumeni‐like syndrome (Calvete et al, 2017) and CRC (Chubb, Broderick, Dobbins, Frampton et al, 2016). Chubb et al, reported the presence of three carriers of Type‐A/B variants among cases: c.219_220insA (p.Asn75LysfsTer16, cpMAF:0%), c.1087C>T (p.Arg363Ter, cpMAF:0.001%) and c.1851_1852delTA (p.Asp617GlufsTer9, cpMAF:0.004%), while no Type‐A/B variants were identified in controls (Chubb, Broderick, Dobbins, Frampton et al, 2016; CanVar).…”
Section: Resultsmentioning
confidence: 99%
“…Although CDKN2A is the primary high-penetrance melanoma predisposition gene,39 40 germline POT1 variants have been reported in melanoma-prone families by several groups 13–18. More than a dozen pathogenic germline mutations of POT1 have been identified in CDKN2A –wild-type melanoma kindreds, distributed across the DNA-binding and TPP1-binding domains.…”
Section: Discussionmentioning
confidence: 99%
“…Because POT1 mutations arise early in CLL pathogenesis, they are believed to function as drivers in disease progression 7–11. Furthermore, germline POT1 mutations have been shown to underlie a number of hereditary familial cancer syndromes involving CLL,11 glioma,12 melanoma13–18 and colorectal cancer 19. Furthermore, a deleterious germline missense variant in POT1 (p. R117C) was identified in three Li-Fraumeni-like families with angiosarcomas,20 and additional POT1 variants were subsequently identified in patients with sporadic angiosarcoma 21…”
Section: Introductionmentioning
confidence: 99%
“…POT1-ΔOB lacks the first OB fold and served as a surrogate for cancer-associated POT1 variants that cannot bind to ssDNA (Loayza and De Lange 2003;Hockemeyer et al 2007;Calvete et al 2015). The K90E substitution did not prevent DNA binding in vitro (Pinzaru et al 2016), but was repeatedly identified in somatic and familial cancers (Quesada et al 2011;Wilson et al 2017), and triggered mild telomere dysfunction (Pinzaru et al 2016). Both alleles retained functional interaction with TPP1 and were efficiently recruited to telomere chromatin (Loayza and De Lange 2003;Pinzaru et al 2016).…”
Section: Genome-wide Crispr Interference Screen Identifies Synthetic mentioning
confidence: 99%